Becoming Writers: Intra-activity with Digital Bookmaking - Toope, Deborah (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2026)
This manuscript draws on data from a collaborative action research project focused on inclusive literacy practices and children’s multimodal meaning making in three primary classrooms. I employ posthumanist conceptual tools of intra-activity and enacted agency to explore how digital technologies and other materials are intertwined in the processes by which young children become writers through digital bookmaking. I illustrate how a posthumanist perspective on literacies enables new understandings and expands possibilities for writing in a digital age. I demonstrate how intra-actions with digital tools and materials create more equitable learning spaces, making new realities possible for enacting knowing/being/doing literacies.